Approach of the Issue of the Quality in Services - Oana VLĂDUŢ; Petruţa MIHAI; Iulian-Claudiu DUŢU; Mihaela-Florentina DUŢU; Maria-Valia MIHAI (Communications of International Proceedings, 2021)
The paper herein merges a theoretical study on the relation between the quality in services and the clients’ satisfaction with a research study, a survey-based inquiry conducted among the clients for the services provided by a company. The aim of this paper is to point out to the satisfaction level for clients of a company. The choice for this topic relies on the considerations that all research studies concerning the client’s satisfaction are focused on understanding how to manage the client’s expectations on the services being provided.
Keywords: Service; Quality; Quality Of Services; Customer Satisfaction.